Distinct Regulation of Sucrose: Sucrose-1-Fructosyltransferase (1-SST) and Sucrose: Fructan-6-Fructosyltransferase (6-SFT), the Key Enzymes of Fructan Synthesis in Barley Leaves: 1-SST as the Pacemaker - Nagaraj, Vinay J.; Altenbach, Denise; Galati, Virginie; Lüscher, Marcel; Meyer, Alain D.; Boller, Thomas; Wiemken, Andres (The New phytologist, 2004)
• Previously we have cloned sucrose: fructan-6-fructosyltransferase (6-SFT) from barley (Hordeum vulgare) and proposed that synthesis of fructans in grasses depends on the concerted action of two main enzymes: sucrose: sucrose-1-fructosyltransferase (1-SST), as in other fructan producing plants, and 6-SFT, found only in grasses. • Here we report the cloning of barley 1-SST, verifying the activity of the encoded protein by expression in Pichia pastoris. As expected, the barley 1-SST is homologous to invertases and fructosyltransferases, and in particular to barley 6-SFT. • The gene expression pattern of 1-SST and 6-SFT, along with the corresponding enzyme activities and fructan levels, were investigated in excised barley leaves subjected to a light-dark regime known to sequentially induce fructan accumulation and mobilization. The turnover of transcripts and enzyme activities of 1-SST and 6-SFT was compared, using appropriate inhibitors. • We found the 1-SST transcripts and enzymatic activity respond quickly, being subject to a rapid turnover. By contrast, the 6-SFT transcripts and enzymatic activity were found to be much more stable. The much higher responsiveness of 1-SST to regulatory processes, as compared with 6-SFT, clearly indicates that 1-SST plays the role of the pacemaker enzyme of fructan synthesis in barley leaves.